Sharia Principles According to Muhammad Asad and Their Significance in Legal Rulings - ahmad nabil amir (Literasi : Jurnal Kajian Keislaman Multi-Perspektif, 2025)
The paper aims to throw lights on Muhammad Asad’s legal thought as expounded in his book This Law of Ours and Other Essays to identify the extent to which Zahiri dogmatic literalism had influenced his legal ideas and interpretation. It seeks to present its underlying philosophy and epistemology of sharī‘ah premises upon plain and direct ordinances of the two fundamental source of Sharī‘ah, the Qur’ān and sunnah (the life-example of the Prophet saw) that constituted the Law of Islam. The study is based on descriptive-qualitative approaches using historical, textual, thematic, semantic, hermeneutical and interpretative method to analyze the data. The finding shows that Muhammad Asad’s cohesive ideas of Islamic law was largely derived from Ibn Hazm’s (d. 456/1064) legal hermeneutic as projected in his voluminous work of Islamic jurisprudence, al-Muhallā. It was structured upon his classical text that inspired his conscious ideas of the spiritual and social aims of the law and its observance as moral habit, and to expound the ideological basis of the sharī‘ah, its nature, meaning and practical implication in the modern context.